Lessons from choice of law in tort in Israel: the rise and fall of the "contacts" approach; the fortuitousness exception and rejection of the common habitual residence exception. (2nd September 2015) - Schuz, Rhona
Abstract : Over the last half a century, the issue of choice of law in tort has dominated academic writing in the field of private international law in the US and has also attracted considerable interest in other common law jurisdictions. It is widely acknowledged that the US has gone too far in embracing flexibility to the exclusion of all certainty and that it is necessary to find a via media between the various US ad hoc approaches and traditional mechanical rigid jurisdiction-selecting rules. Whilst the EU Rome II Regulation can be seen as progress in the right direction, some of its provisions have attracted criticism and so the search for the optimal solution is by no means over. This article is based on the assumption that an analysis of Israeli developments in relation to choice of law in tort will be of value to both Americans and Europeans. The fact that the trends in Israeli case-law have been strongly influenced, at different stages, by the developments in both the US and Europe makes the perspective of the Israeli courts of particular interest and makes the evaluation of the US and European methodologies through the prism of the specific factual situations which have arisen in Israeli case-law especially instructive. The article will analyse three interwoven aspects of choice of law in tort in Israeli case-law over the past three decades. The first is the rise and fall of the "contacts approach." A fascinating characteristic of the reported Israeli case-law, during the period in which a US-style flexible approach was applied to choice of law in tort, is that most of it involves a particular recurring fact situation, involving Palestinians injured while working for Israeli employers on the West Bank. The second aspect is the creation by the Israeli Supreme Court (SC) of an exception to the lex loci delicti rule based on the fortuitousness of the connection between the tort and the locus delicti . Whilst reference to fortuitousness can be found in scholarly writing and judgments in other countries, no attempt seems to have been made hitherto to define the concept in the choice of law context. After mapping and characterizing various models of fortuitousness, the article analyses to what extent an exception based on fortuitousness, in the various possible senses, is likely to be consistent with central choice of law objectives. The third aspect is the rejection by a majority of the Israeli SC of the common habitual residence exception to the application of the lex loci delicti. The various arguments put forward by the Israeli SC judges in favour of and against such an exception provide the backdrop to an analysis of the extent to which a common habitual residence rule or exception does indeed promote central choice of law objectives. Finally, the article draws together the various threads and suggests what lessons might be learnt in relation to choice of law in tort from the Israeli experience.